2003
DOI: 10.1097/01.mp.0000051930.68104.92
|View full text |Cite
|
Sign up to set email alerts
|

Lobular Carcinoma In Situ Diagnosed By Core Needle Biopsy: When Should It Be Excised?

Abstract: Core needle biopsy is the preferred technique for evaluating breast masses and abnormal mammographic findings. The frequency of detection of noninvasive lobular lesions by core needle biopsy is increasing. Historically, the diagnosis of lobular carcinoma in situ has been considered a risk factor for the development of invasive carcinoma, and treatment has consisted of careful clinical follow-up with or without chemopreventive therapeutic agents such as tamoxifen citrate. We retrospectively reviewed core needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
3
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 17 publications
3
71
3
3
Order By: Relevance
“…Overall, a review of the radiologic findings for the 16 patients who had a final diagnosis of breast carcinoma failed to reveal any consistent distinguishing features. Therefore, unlike Middleton et al, 30 we were unable to establish any criteria for ruling out follow-up excisional biopsy on the basis of initial mammographic findings.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Overall, a review of the radiologic findings for the 16 patients who had a final diagnosis of breast carcinoma failed to reveal any consistent distinguishing features. Therefore, unlike Middleton et al, 30 we were unable to establish any criteria for ruling out follow-up excisional biopsy on the basis of initial mammographic findings.…”
Section: Discussionmentioning
confidence: 79%
“…Middleton et al 30 recently published a report on 35 patients diagnosed with LN on core biopsy. Seventeen of these patients subsequently underwent excisional biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the radiology-pathology correlation data are either missing or incomplete in many studies. 4 Studies that have included radiology-pathology correlation for core biopsy cases with papillomas 22,23 and lobular neoplasia [24][25][26] tend to report lower upgrade rates and may argue against mandatory excision for these diagnoses on core biopsy. Similarly, our overall upgrade rate of 7% for cases with careful correlation is lower than the majority of published studies with 30 or more excisions (Table 4) and closer to the 9.5% reported by Bianchi et al 27 in a series of 589 cases from multiple hospitals in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it seems prudent to offer excision to patients with a core biopsy diagnosis of flat epithelial atypia with limited sampling of the radiographic target or discordant imaging findings, similar to what has been proposed for solitary papillomas and lobular neoplasia diagnosed on core biopsy. [24][25][26] Most studies evaluating the upgrade rates of flat epithelial atypia on core biopsy have not reported the characteristics of the carcinoma upgrades identified on excision. As this study demonstrates, flat epithelial atypia is associated with other forms of low-grade atypia and low-grade estrogen receptorpositive carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases included in previously published studies (combining atypical lobular hyperplasia and lobular carcinoma in situ) varies from less than 10 up to 92 cases of lobular neoplasia followed by immediate excision. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In comparison, our study includes a relatively high number of cases (87 cases of lobular neoplasia followed by immediate excision). Another limitation in our study and others is that it is retrospective and may suffer from selection bias regarding the patients that underwent excision.…”
Section: Discussionmentioning
confidence: 99%